Impact of Corporate Governance and Macroeconomics Volatility on Capital Structure Decisions - Aslam, Maryam; Hamid, Kashif; Ahmad, Waseem; Naeem, Mariam (International Journal of Business and Economic Affairs, 2024)
Presently the role of corporate governance and macroeconomic factors has increased the importance of corporate financial decisions. Capital structure decisions are one of the main corporate financial decisions. The aim of the present study is to investigate the effect of corporate governance and macroeconomic volatility on firm`s capital structure decisions. This study focused on Energy and Fuel sector and panel data was used for the period 2005-2018. The econometric analysis concluded that lagged leverage have positive significant influence on leverage and the size of the firm have negative significant impact on leverage. Assets efficiency and inflation have positive impact on leverage but Dummy for Crises has negative impact on leverage. Moreover, study observes that overall impact of macroeconomic volatility on the firm leverage with the improved governance qualities resulted as negative. The evidence recommends that governance perform as helpful mechanism to control the usage of firm`s leverage throughout period of high fluctuations. This study is beneficial for the investors, corporate decision makers and public policy makers.